Resolving the micro-heterogeneity and structural integrity of monoclonal antibodies by hybrid mass spectrometric approaches. Issue 4 (19th May 2017) - Yang, Yang; Wang, Guanbo; Song, Ting; Lebrilla, Carlito B.; Heck, Albert J. R.
ABSTRACT: For therapeutic monoclonal antibodies (mAbs), detailed analysis of the structural integrity and heterogeneity, which results from multiple types of post-translational modifications (PTMs), is relevant to various processes, including product characterization, storage stability and quality control. Despite the recent rapid development of new bioanalytical techniques, it is still challenging to completely characterize the proteoform profile of a mAb. As a nearly indispensable tool in mAb analysis, mass spectrometry (MS) provides unique structural information at multiple levels. Here, we tested a hybrid strategy for the comprehensive characterization of micro-heterogeneity by integrating 2 state-of-the-art MS-based approaches, high-resolution native MS and targeted glycan profiling, to perform complementary analysis at the intact protein level and released glycan level, respectively. We compared the performance of these methods using samples of engineered half-body IgG4s and a panel of mAbs approved for human use. The glycosylation characterization data derived from these approaches were found to be mutually consistent in composition profiling, and complementary in identification and relative-quantitation of low-abundant uncommon glycoforms. In addition, multiple other sources of micro-heterogeneity, such as glycation, lack of glycosylation, and loss of light chains, could be detected by this approach, and the contribution of multiple types of modifications to the overall micro-heterogeneity could be assessed using our superposition algorithm. Our data demonstrate that the hybrid strategy allows reliable and thorough characterization of mAbs, revealing product characteristics that would easily be missed if only a single approach were used.